2019
DOI: 10.1111/tbj.13277
|View full text |Cite
|
Sign up to set email alerts
|

Neo‐adjuvant chemotherapy does not affect the immediate postoperative complication rate after breast reconstruction

Abstract: Neo-adjuvant chemotherapy (NAC) refers to systemic therapy for breast cancer (BC) prior to definitive surgical treatment and is proved safe and effective. The purpose of administering NAC is to downstage the tumor, allowing for less extensive surgery and improved cosmetic outcomes. [1][2][3][4] While originally intended for patients with locally advanced BC, for whom even a mastectomy may not be feasible, NAC is now frequently administered to patients with operable BC, in attempt to improve cosmetic outcomes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…A total of 134,191 patients (136,326 breasts) were included, of which 9,678 patients (10,571 breasts) were treated with NACT and 124,516 patients (125,696 breasts) were not treated with NACT and thus represented the control group. Three studies [20e22] only reported number of breasts while two studies [23,24] only reported number of patients. To increase the comparability of the studies, the complication rates based on breasts and patients were analysed individually.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 134,191 patients (136,326 breasts) were included, of which 9,678 patients (10,571 breasts) were treated with NACT and 124,516 patients (125,696 breasts) were not treated with NACT and thus represented the control group. Three studies [20e22] only reported number of breasts while two studies [23,24] only reported number of patients. To increase the comparability of the studies, the complication rates based on breasts and patients were analysed individually.…”
Section: Resultsmentioning
confidence: 99%
“…The complication rate in this series (35%) may be partially explained by our high rate of smokers (20%), prior radiation treatment (XRT) (11%), and alloplastic reconstruction (70%). In a previous publication 27 based on an overlapping dataset, we found that alloplastic reconstruction had a higher complication rate compared with autologous reconstruction.…”
Section: Discussionmentioning
confidence: 72%
“…The major complications identi ed were partial or total ap loss, venous congestion, infection, hematoma, seroma, fat necrosis, and wound dehiscence. Thirteen studies concluded there was no signi cant difference in the complication rates of patients who received NST and those who did not [3,5,12,13,21,22,24,26,31,35,43,44,46,49]. In the pooled analysis, when comparing BRS complications with and without NST, the overall NST patient complication rates were higher (10.61%), but not statistically signi cant (NST = 44.07 %, Control = 33.46%, P=0.21).…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Eight of the studies were conducted in the United States of America [9,13,21,29,41,42,44,46]. One study was translated into English from Hebrew [22]. Fifteen studies had patients with ap reconstruction surgery [3,22,26,29,30,31,35,43,44,49], six studies had patients with both ap and implant reconstruction surgery [9,12,13,21,42,46] and two studies had patients with implant reconstruction surgery [5,24].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation